Interactions and Feedbacks in E-Cadherin Transcriptional Regulation - Ramirez Moreno, Miguel; Stempor, Przemyslaw A.; Bulgakova, Natalia A. (Frontiers in Cell and Developmental Biology, 2021)
Epithelial tissues rely on the adhesion between participating cells to retain their integrity. The transmembrane protein E-cadherin is the major protein that mediates homophilic adhesion between neighbouring cells and is, therefore, one of the critical components for epithelial integrity. E-cadherin downregulation has been described extensively as a prerequisite for epithelial-to-mesenchymal transition and is a hallmark in many types of cancer. Due to this clinical importance, research has been mostly focused on understanding the mechanisms leading to transcriptional repression of this adhesion molecule. However, in recent years it has become apparent that re-expression of E-cadherin is a major step in the progression of many cancers during metastasis. Here, we review the currently known molecular mechanisms of E-cadherin transcriptional activation and inhibition and highlight complex interactions between individual mechanisms. We then propose an additional mechanism, whereby the competition between adhesion complexes and Heterochromatin Protein-1 for binding to STAT92E fine-tunes the levels of E-cadherin expression in Drosophila but also regulates other genes promoting epithelial robustness. We base our hypothesis on both existing literature and our experimental evidence and suggest that such feedback between the cell surface to the nucleus presents a powerful paradigm for epithelial resilience.